"How much life can I give?" - How artists with side jobs experience and create the value of work - Pertmann,Klara (2026)
This thesis explores how performance artists with side jobs create and experience the value of work in relation to neoliberal capitalism, by exploring the continuation of life projects not in line with hegemonic values and conventional work-life boundaries. Through interviews with 8 key informants, and participant observation in work contexts and at a cultural hub for creatives, the study recognises how production processes constitute connections between work contexts, artist/worker-persons, and receivers of performed work. Using theory from Graeber on value, Mauss on The Gift, Lynch on care work and love labour, Lepecki on performance art, and borrowing terminology from Deleuze & Guattari, enables an analysis of how social structure and personal artistic practice are intertwined. The analysis considers the experienced and created value of artistic work and non-artistic side jobs, and how artists produce as a rhizomatic bricolage, using imagination and scrambling codes of their surroundings. Underlining, is an exploration of desires and needs, and how the precarity, exploitation, and devaluation inherent to artistic and service-based work, is handled by workers. The conclusion shows artists with side jobs use creativity to live a life they value - a life of human relations both in normality and imagination, through the care work and love labour of gift-giving.
Keywords: value; work; performance art; side jobs; dance; social anthropology